A WhatsApp-Based Application for Automatic Data Collection and Crime Monitoring in Belo Horizonte - Fonseca, Gustavo Silva da; Patrício, Guilherme S.; Ferreira, Carlos H. G.; Sousa, Alexandre M. de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This work presents the development of a crime monitoring system for Belo Horizonte based on the automatic collection of messages from public WhatsApp groups. The system adopts a modular and scalable architecture, integrating services for filtering, structuring and storing data in a hierarchical database that supports queries by region, neighborhood and time period. Crimes are identified in two steps: (1) an initial filter detects potential crime-related messages using a predefined dictionary of keywords, and (2) a Machine Learning model classifies the messages with higher accuracy. This automated pipeline ensures continuous data processing without manual intervention and provides up-to-date geographic information on crimes. The proposed framework demonstrates the feasibility of using instant messaging platforms for real-time crime monitoring and offers scalability and adaptability for application in other cities and related data monitoring contexts.